Challenges and Strategies in the Implementation of the International Patient Summary in Accordance with International Standards: A Systematic Review - Oliveira, Adicinéia Aparecida de; Frade, Samuel; Vieira-Marques, Pedro; Jacinto, Tiago António Queirós; Homem-Silva, Patrícia; Lemos-Sebasteão, Susana; Oliveira, Celeste M. G. Marques de; Ferreira e Sousa, Liliane F. A.; Rocha, Jéssica Cristina Oliveira; Cruz-Correia, Ricardo João (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: The growing international movement of people necessitates adopting interoperable health data solutions like the International Patient Summary (IPS). Diverse standards, terminologies, and specifications require significant efforts to achieve agility, interoperability, compliance, security, and privacy. Problem: Few studies discuss the challenges and strategies for implementing the IPS in compliance with international standards; additionally, many professionals are unaware of the benefits of compliance, hindering adoption. Solution: This study aims to identify challenges, barriers, strategies, and success factors in IPS implementation, emphasizing interoperability, technical specifications, and health standards. IS Theory: Anchored in Sociotechnical Theory, the study examines how the interaction between technical components (international standards, interoperability) and social components (regulations, collaboration, clinical routines) influences IPS implementation. Method: A systematic review following the PRISMA 2020 protocol identified 43 relevant studies, analyzed quantitatively and qualitatively to consolidate information on compliance standards, challenges, and strategies. Summary of Results: Key challenges include harmonizing international standards, ensuring patient data privacy and security, and interoperability among heterogeneous systems. Effective strategies involve developing harmonized implementation guides and collaboration among standardization organizations like ISO, HL7, and CEN. Contributions and Impacts in the IS area: This study underscores the importance of a sociotechnical approach in IPS implementation per international standards, contributing to public policies and the development of health information systems that integrate technological and organizational aspects, promoting interoperability, security, and privacy of health data.